[Rezension von: F.S. Naiden, Soldier, priest, and god. A life of Alexander the Great] - Trampedach, Kai (De Gruyter, 2022)
F.S. Naiden, Soldier, priest, and god. A life of Alexander the Great], Oxford - New York (Oxford University Press) 2019, 424 S., ISBN 978-0-19-087534-3 (geb.), £ 20,99